Distribution and estimation of washed out seaweeds biomass in Oman Sea coastal waters - B.M Gharanjik email ; Bahareh Nazari; B Saeedpour; T valinassab (‬‭Majallah-i ̒Ilmī-i Shīlāt-i Īrān, 2016)
This study was carried out to determine the Seaweed biomass in the coast of Sistan & Baluchestan Province. Beris, Chabahar, Pozm and Tang were introduces as high density zones and Jood & Lipar were selected as low density zones.